Reconstructing the landscape evolution and the human occupation of the Lower Sagone River (Western Corsica, France) from the Bronze Age to the Medieval period. (April 2017) - Ghilardi, Matthieu; Istria, Daniel; Curras, Andrés; Vacchi, Matteo; Contreras, Daniel; Vella, Claude; Dussouillez, Philippe; Crest, Yannick; Guiter, Frédéric; Delanghe, Doriane
Abstract: This paper aims to reconstruct the landscape evolution together with the vegetation history of the lower Sagone Valley, Western Corsica, which was occupied from the Bronze Age to the Medieval Period. Adopting a geoarchaeological approach, the combination of sedimentological, palynological, and geophysical data enables the reconstruction of various stages in the landscape evolution of the Lower Sagone River over the last 4000 years, together with the history of human occupation. The methods consist of a palaeoenvironmental study of 9 boreholes drilled in the modern deltaic plain, at a maximum distance of 500 m from the present-day shoreline. The laboratory analyses included mollusk identification and measurements of the grain-size distribution (by wet sieving). A series of 21 radiocarbon dates on charcoal, plant remains, wood fragments, and marine mollusk samples formed the basis for a chronostratigraphy. In order to reconstruct the vegetation history of the catchment, with particular attention to anthropogenic activity, pollen analysis was conducted on clay samples from the deepest borehole, and they revealed a semi-open forest during the Bronze Age and Late Iron Age with extensive pastoral activity and limited cereal cultivation. Electric Resistivity Tomography (ERT) of 3 profiles across the alluvial plain was conducted in order to reveal the geometry of the sedimentary bodies. The salient features are the presence of a freshwater lake during the Mid- to Late Bronze Age (from 1500 to 1100 cal. BCE), its transformation into an open marine bay from ca. 1100 until 500 cal. BCE, and the formation of a confined lagoon from 500 cal. BCE to 200 cal. CE. Highlights: First palaeogeographic reconstruction led in a corsican coastal plain based on corings and geophysics Existence of a freshwater lake until the Late Bronze Age in the Lower Sagone Valley A deltaic progradation of the Sagone River occurred from the 1st Millennium BC onward Vegetation history of the Late Bronze Age and Roman times do not reveal important human activies, only local pastoralism